Unusual Presentation of a Sigmoid Mass with Chicken Bone Impaction in the Setting of Metastatic Lung Cancer - Ziad Zeidan; Zarnie Lwin; Harish Iswariah; Sheyna Manawwar; Anitha Karunairajah; Manju Dashini Chandrasegaram (Case Reports in Surgery)
Background. Ingestion of foreign bodies can cause various gastrointestinal tract complications including abscess formation, bowel obstruction, fistulae, haemorrhage, and perforation. While these foreign body-related complications can occur in normal bowel, diseased bowel from inflammation, strictures, or malignancy can cause diagnostic difficulties. Endoscopy is useful in visualising the bowel from within, providing views of the mucosa and malignancies arising from here, but its ability in diagnosing extramural malignancies arising beyond or external to the mucosa of the bowel as in the case of metastatic extramural disease can be limited. Case Summary. We present the case of a 60-year-old female with an impacted chicken bone in the sigmoid colon with formation of a sigmoid mass, on a background of metastatic lung cancer. On initial diagnosis of her lung cancer, there was mild Positron Emission Tomography (PET) avidity in the sigmoid colon which had been evaluated earlier in the year with a colonoscopy with findings of diverticular disease. Subsequent computed tomography (CT) scans demonstrated thickening of the sigmoid colon with a structure consistent with a foreign body distal to this colonic thickening. A repeat PET scan revealed an intensely fluorodeoxyglucose (FDG) avid mass in the sigmoid colon which was thought to be inflammatory. She was admitted for a flexible sigmoidoscopy and removal of the foreign body which was an impacted chicken bone. She had a fall and suffered a fractured hip. During her admission for her hip fracture, she had an exacerbation of her abdominal pain. She developed a large bowel obstruction, requiring laparotomy and Hartmann’s procedure to resect the sigmoid mass. Histopathology confirmed metastatic lung cancer to the sigmoid colon. Conclusion. This unusual presentation highlights the challenges of diagnosing ingested foreign bodies in patients with metastatic disease.